Pengaruh tekanan, kesempatan dan rasionalisasi keuangan terhadap manajemen laba - Saputra, Andhika; Hermanto, Hermanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to determine the effect of pressure, opportunity and financial rationalization on earnings management with financial stability, external pressure, financial targets as a proxy for pressure, the nature of the industry and effective monitoring as a proxy for opportunity and rationalization. The research method uses this type of research which is basic research, and the data analysis method used in this study is multiple linear regression. This study utilizes data taken from the financial statements of manufacturing companies with the food and beverage sub-sector that have been recorded and listed on the Indonesia Stock Exchange using a sampling technique that uses purposive sampling to meet the research criteria. The research period used is 6 years with a total sample data used of 84 of 14 manufacturing entities in the food and beverage sub-sector. This study uses multiple linear analysis methods with secondary data types. The results of the study show that financial targets have a negative effect on earnings management, effective monitoring and rationalization have a positive effect on earnings management, while financial stability, external pressure and the nature of the industry have no effect on earnings management